2013
DOI: 10.1186/1752-0509-7-9
|View full text |Cite
|
Sign up to set email alerts
|

Signaling dynamics of palmitate-induced ER stress responses mediated by ATF4 in HepG2 cells

Abstract: BackgroundPalmitic acid, the most common saturated free fatty acid, has been implicated in ER (endoplasmic reticulum) stress-mediated apoptosis. This lipoapotosis is dependent, in part, on the upregulation of the activating transcription factor-4 (ATF4). To better understand the mechanisms by which palmitate upregulates the expression level of ATF4, we integrated literature information on palmitate-induced ER stress signaling into a discrete dynamic model. The model provides an in silico framework that enables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 42 publications
(58 reference statements)
4
35
0
1
Order By: Relevance
“…We also found that palimtic acid induces ATF4 and FGF21 gene expression in FaO cells, while oleic acid increased gene expression of FGF21 but not ATF4. Based on previous reports showing the positive effect of palmitic acid on ATF4 expression and that of oleic acid on PPARα transcriptional activity [24], [25], we speculate that FFAs released from adipose tissue by acute exercise-induced lipolysis both induce gene expression of ATF4 and enhance the transcriptional activity of PPARα in the liver, leading to the synergistically increased hepatic FGF21 expression.…”
Section: Discussionsupporting
confidence: 58%
“…We also found that palimtic acid induces ATF4 and FGF21 gene expression in FaO cells, while oleic acid increased gene expression of FGF21 but not ATF4. Based on previous reports showing the positive effect of palmitic acid on ATF4 expression and that of oleic acid on PPARα transcriptional activity [24], [25], we speculate that FFAs released from adipose tissue by acute exercise-induced lipolysis both induce gene expression of ATF4 and enhance the transcriptional activity of PPARα in the liver, leading to the synergistically increased hepatic FGF21 expression.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, NLRC4 and ASC levels are upregulated in the brains of AD patients (Liu and Chan, 2014), suggesting a possible role of the NLRC4 inflammasome in AD pathogenesis. In support, palmitate induces IL-1β release from HepG2 (hepatocellular carcinoma cells), and knockdown of NLRC4 inhibits the palmitate induced inflammation and cytokine release (Cho et al, 2013; Luo et al, 2012). Fatty acids can also cause the release of IL-1β from microglia, but the specific inflammasome that regulates this process has not been identified (Wang et al, 2012).…”
Section: Fatty Acids Involvement In Inflammasome Activation and Pamentioning
confidence: 95%
“…Elevated blood levels of NEFA are considered important inducers of ER stress in the liver, based on the observation that metabolic conditions associated with elevated plasma NEFA levels, such as obesity or diabetes, lead to ER stress in the liver (Kharroubi et al., ; Cnop et al., ; Kawasaki et al., ). Obviously, this effect is dependent on the type of fatty acids, because saturated fatty acids produce ER stress in several cell types, including hepatocytes, whereas unsaturated fatty acids do not (Borradaile et al., ; Wei et al., ; Cho et al., ). In line with this, infusion of lard oil (enriched in saturated fatty acids) resulted in a stronger induction of ER stress in the liver than soybean oil (enriched in unsaturated fatty acids; Nivala et al., ).…”
Section: Role Of Er Stress For Fatty Liver and Ketosis Developmentmentioning
confidence: 99%